How Does Renewable Energy Consumption Affect Environmental Quality in Saudi Arabia? Evidence from Quantile Regressions - Abid, Mehdi (International Journal of Energy Economics and Policy, 2023)
This paper explores the relationship between renewable energy consumption, non-renewable energy, economic growth and urbanization on CO2 emissions of Saudi Arabia during 1990–2019 period. Using the OLS method and the quantile approach developed by Powell (2022), the results prove that the consumption of renewable energy significantly reduces the level of CO2 emissions; moreover, its impact increases with higher quantiles. On the other hand, non-renewable energy consumption increases CO2 emissions, while its effect decreases with higher quantiles. The empirical results also confirm the validity of the EKC hypothesis for the case of Saudi Arabia. Policymakers should implement policies and regulations to promote the adoption and use of renewable energy to improve environmental quality.